Perancangan Otomasisasi Pengisian Baterai Dengan Surber Energi Surya - Hanggun Syahadad; Azriyenni Azhari Zakri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A charger controller is required in the process of charging batteries that use solar energy through solar panels. The battery charging process can use more than one battery, in this study using two batteries. For this reason, it is necessary to design a battery charging automation device with a solar energy source to facilitate the battery charging process. The charging method is run alternately on two batteries that will be charged based on the preset low voltage sensor. The initial voltage value on the battery is used to calculate the battery's State of Charge (SOC) capacity. In this study, we will observe the filling process of two batteries of 12 Volt Lead Acid types, having a battery capacity of 3.5 Ah and 7.2 Ah with a source of 100 Wp solar panels. An Arduino microcontrollers is invoked as control systems for reading voltage and current sensors as detectors during battery charging. The test results obtained that the first battery is filled with 12.3 Volt for battery voltage at 69.4% SOC reading, then 12.82 Volt second battery with 84.9% SOC reader. The duration of the first battery charging is for 90 minutes with an average current value of 0.7 Ampere at 100% battery of SOC. The second battery starts charging after the battery is full when the relay has moved automatically to charge the second battery. The duration of second battery is charging for 60 minutes with an average current of 0.17 Ampere at 94% SOC. All measurement results, during the test are run directly recorded by the data logger and stored on the SD Card.Keywords: Arduino, Control Charge, Data Logger, Current Sensor, Voltage Sensor